DNA damage stabilizes interaction of CSB with the transcription elongation machinery - van den Boom, Vincent (The Rockefeller University Press, 2004)
The Cockayne syndrome B (CSB) protein is essential for transcription-coupled DNA repair (TCR), which is dependent on RNA polymerase II elongation. TCR is required to quickly remove the cytotoxic transcription-blocking DNA lesions. Functional GFP-tagged CSB, expressed at physiological levels, was homogeneously dispersed throughout the nucleoplasm in addition to bright nuclear foci and nucleolar accumulation. Photobleaching studies showed that GFP-CSB, as part of a high molecular weight complex, transiently interacts with the transcription machinery. Upon (DNA damage-induced) transcription arrest CSB binding these interactions are prolonged, most likely reflecting actual engagement of CSB in TCR. These findings are consistent with a model in which CSB monitors progression of transcription by regularly probing elongation complexes and becomes more tightly associated to these complexes when TCR is active.